Knowledge and Attitudes Toward Electroconvulsive Therapy Among Companions of Psychiatric Patients: A Cross-Sectional Study from Northern Iran, Rasht - Ali Pourramzani; Zahra Fallah; Maryam Nasseri Alavi; Zahra Atrkarroushan; Nazanin Rahmanian (Journal of Iranian Medical Council, 2026)
Background: Electroconvulsive Therapy (ECT) is a highly effective treatment for psychiatric disorders, particularly in emergency cases, pregnancy, and when pharmacological treatments are contraindicated. However, misconceptions and negative attitudes among patients’ companions can hinder its acceptance and adherence. This study aimed to evaluate the knowledge and attitudes of companions of ECT recipients at Shafa Hospital in 2024. Methods: A cross-sectional descriptive study was conducted among companions of psychiatric patients referred to Shafa Hospital in Rasht, Iran during 2024. The data collection tool is a questionnaire measuring knowledge and attitudes related to ECT. The variables analyzed using mean, standard deviation (SD), frequency and a significance level of p